Predictors of physical activity following gestational diabetes: Application of health action process approach - Banafsheh Mohammadi Zeidi; Nourossadat Kariman; Zahra Kashi; Isa Mohammadi Zeidi; Hamid Alavi Majd (Wiley, 2020)
Abstract Aim Regular physical activity can reduce the chance of developing type 2 diabetes in women with a history of gestational diabetes. The present study investigated the relationship between the constructs of the health action process approach and regular physical activity in women with a history of gestational diabetes. Design This was a cross‐sectional study. Methods A total of 150 women who had given birth 6-24 months prior to the study and had experienced gestational diabetes in their recent pregnancy were selected using multistage cluster sampling. Data were collected from December 2018 to May 2019 using a researcher‐made questionnaire including constructs of health action process approach. Results The common fit indices revealed that health action process approach had an acceptable fit to the observations (root mean square error of approximation = 0.054, Tucker-Lewis index = 0.95, comparative fit index = 0.955). The model's constructs predicted 48% of intention variance and 35% of physical activity variance. Action self‐efficacy and coping planning were the most important predictors of intention and behaviour, respectively.